A rational design of layered metal–organic framework towards high-performance adsorption of hazardous organic dye. Issue 22 (18th May 2021) - Guo, Dan-Dan; Li, Bo; Deng, Zhao-Peng; Huo, Li-Hua; Gao, Shan
Abstract : Acid–base stably layered L-MOF-1 has been prepared, which exhibits high adsorption capacity of 12 000 mg g −1 in 20 min in the pH range of 2.2–4.7 to CR, representing the best adsorbent with largest capacity and fastest adsorption for CR to date. Abstract : Water pollution originating from organic dyes is endangering the survival and development of society; however, adsorbents with high capacity (>5000 mg g −1 ) for the fast removal (≤30 min) of Congo Red (CR) in aqueous solution have been not reported to date. In the present work, an acid–base stably layered MOF, [Cd(H2 L)(BS)2 ] n ·2nH2 O (L-MOF-1, H2 L = N 1, N 2-bis(pyridin-3-ylmethyl)ethane-1, 2-diamine, BS = benzenesulfonate), was hydrothermally prepared. L-MOF-1 exhibited high-performance adsorption of CR in aqueous solution at room temperature. The experimental adsorption capacity of the L-MOF-1 adsorbent towards CR reached up to about 12 000 mg g −1 in 20 min in the pH range of 2.2–4.7, which is the best adsorbent with the highest capacity and fastest adsorption of CR to date. The spontaneous adsorption process can be described by the pseudo-second-order kinetic and Langmuir isotherm models. Meanwhile, the L-MOF-1 absorbent possessed a highly positive zeta potential in acid condition (even at pH = 2.2, zeta potential = 36.2 mV). Its good adsorption performance mainly originates from its strong electrostatic attraction with CR in acidic condition, together with diverse hydrogen bonds and π⋯π stacking interactions. Furthermore, the L-MOF-1 absorbent exhibited good selectivity and could be reused five times through simply washing, where its adsorption efficiency was hardly affected. Therefore, L-MOF-1 is a potential absorbent for effectively removing CR from dye wastewater.